Book Review (The Muslim world, 1989)
Book reviewed in this article: The Vatican, Islam and the Middle East. Edited by Kail C. Ellis. Syracuse: Syracuse University Press, 1987, 336 pp. USD39.95, cloth. My Friend the Enemy. By Uri Avnery. Westport, CT: Lawrence Hill and Co., 1986. 340 pp. USD19.95, cloth; USD12.95, paper. The Armenian Genocide in Perspective. Edited by Richard G. Hovannisian. New Brunswick, N.J.: Transaction Books, 1986. 203 pp., index. n.p. A Share of the Harvest: Kinship, Property, and Social History Among the Malays of Rembau. By Michael Gates Peletz. Berkeley: University of California Press, 1988. xxv plus 383 pp. Photographs. Maps. Tables. Charts. Bibliography. Indices. USD39.95. Back to the Fold? Egypt and the Arab World. By Abdel Monem Said Aly. Washington, D.C.: Center for Contemporary Arab Studies, September, 1988. Occasional Paper Series. 22 pp. n.p. Modern Egypt: The Formation of a Nation-State. By Arthur Goldschmidt, Jr. Boulder, Colorado: Westview Press, 1988. x plus 211 pp. USD32.00, hardcover; USD14.95, paper. The Munshidin of Egypt. Their World and their Song. By Earle H. Waugh. Columbia: University of South Carolina Press, 1989. xvii plus 246 pp. A House of Many Mansions: The History of Lebanon Reconsidered. By Kamal Salibi. Berkeley, CA: University of California Press, 1988. 247 pp. USD22.50. Murder, Mayhem, Pillage, and Plunder: The History of the Lebanon in the 18th and 19th Centuries. By Mikhǎyil Mishǎga. Translated from the Arabic by W. M. Thackston, Jr. Albany, N.Y.: State University of New York Press, 1988. xix plus 309 pp. Photographs. Maps. Appendices. Index. USD16.95, paper; USD49.50, cloth. A History of the Jews of Arabia from Ancient Times to Their Eclipse under Islam. By Gordon Darnell Newby. [Studies in Comparative Religion. Edited by Frederick M. Denny.] Columbia, South Carolina: University of South Carolina Press, 1988. xii plus 177 pp. Map. Index. n.p. Palestinians in the Arab World: Institution Building and the Search for State. By Laurie A. Brand. New York: Columbia University Press, 1988. 286 pp. USD35.00. The Birth of the Palestinian Refugee Problem, 1947-1949. By Benny Morris [Cambridge Middle East Library.] New York: Cambridge University Press, 1987. xx plus 380 Maps. Bibliography. Index. USD39.50, hardcover. Islam and Revolution in the Middle East. By Henry Munson, Jr. New Haven and London: Yale University Press, 1988. xi plus 180 pp. Footnotes, Bibliography, and Index. USD18.95. Christian Martyrs in Muslim Spain. By Kenneth Baxter Wolf. Cambridge: Cambridge University Press, 1988. xi plus 145 pp. Bibliography. Index. n.p. The Prophet and the Age of the Caliphate: The Islamic Near East from the Sixth to the Eleventh Century. By Hugh Kennedy. London and New York: Longman, 1986. xii plus 424 pp. n.p. Islamic Values in the United States: A Comparative Study. By Yvonne Yazbeck Haddad and Adair T. Lummis. New York: Oxford University Press, 1987. viii plus 196 pp. Charts. Tables. Bibliography. Index. USD24.95. (USD9.95 paper). An Introduction to Religious Foundations in the Ottoman Empire. By John Robert Barnes. Leiden: E. J. Brill, 1986. xii plus 156 pp. Bibliography. USD29.00. Der Islam im Spiegel westlicher Theologie: Aspekte christlich-theologischer Beurteilung des Islams im 20 Jahrhundert. By Klaus Hock. [Kölner Veröffentlichungen zur Religionsgeschichte herausgegeben von Michael Klöcker und Udo Tworuschka, Band 8]. Köln; Wien: Böhlau Verlag, 1986. 403 pp. Bibliography. n.p. The History of al-Tabari (Trikh al-rusul wl-muluk) vol. VI Muhammad at Mecca. Translated and annotated by W. Montgomery Watt and M. V. McDonald. [Bibliotheca Persica.] Albany, New York: State University of New York Press, 1988. xlvi plus 178 pp. USD44.50, cloth; USD14.95, paper. Shiism: Doctrines, Thought, and Spirituality. Edited, Annotated, and with an Introduction by Seyyed Hossein Nasr, Hamid Dabashi, and Seyyed Vali Reza Nasr. Albany, N.Y.: State University of New York Press, 1988. xviii plus 401 pp. USD24.50, paper; USD73.50, cloth. Islamic Awakening Between Rejection and Extremism. By Yusuf al-Qaradawi. [Issues of Islamic Thought Series No. 2.] Herndon, Va.: American Trust Publication and the International Institute of Islamic Thought. n.d., 123 pp., n.p. The Banners of the Champions. An Anthology of Medieval Arabic Poetry from Andalusia and Beyond. By Ibn Said al-Maghrib. Selected and translated by James A. Bellamy and Patricia Owen Steiner. Madison: Hispanic Seminary of Medieval Studies, 1989. xxxix plus 238 pages. Bibliography. Brief Biographies. Index of Images. n.p. Seed of Redemption: A Political Novel. By Francis Mading Deng. New York: Lilian Barber Press, 1986. xi plus 304 pp. USD17.95. Health and Medicine in the Islamic Tradition. By Fazlur Rahman. New York: The Crossroad Publishing Company, 1987. xiii plus 149 pp. USD18.95. Averroes’ Middle Commentary on Aristotle's “Poetics.“ Translated, with Introduction and Notes, by Charles E. Butterworth. Princeton: Princeton University Press, 1986. xvi plus 161 pp. Bibliography. Arabic-English and English-Arabic Glossaries. Index. USD22.50. Arabic Philosophy and the West. Edited by Therese-Anne Druart. Washington, D.C.: Center for Contemporary Arab Studies, Georgetown University, 1988. ix plus 263 pp. Index. n.p.